Fugitives : A History of Nazi Mercenaries During the Cold War - Orbach, Danny 1981- (C Hurst & Co Publishers Ltd, 2024)
From Spain to Syria, the thrilling, untold history of Nazi fugitives turned postwar agents-for America, the Soviets, the Third World, or themselves